Understanding the psychosocial experiences of adults with mild-moderate hearing loss: an application of Leventhal’s self-regulatory model - Heffernan, Eithne; Coulson, Neil S.; Henshaw, Helen; Barry, Johanna G.; Ferguson, Melanie A. (Taylor & Francis, 2016)
Objective: This study explored the psychosocial experiences of adults with hearing loss using the self-regulatory model as a theoretical framework. The primary components of the model, namely cognitive representations, emotional representations, and coping responses, were examined. Design: Individual semi-structured interviews were conducted. The data were analysed using an established thematic analysis procedure. Study sample: Twenty-five adults with mild-moderate hearing loss from the UK and nine hearing healthcare professionals from the UK, USA, and Canada were recruited via maximum variation sampling. Results: Cognitive representations: Most participants described their hearing loss as having negative connotations and consequences, although they were not particularly concerned about the progression or controllability/curability of the condition. Opinions differed regarding the benefits of understanding the causes of one’s hearing loss in detail. Emotional representations: negative emotions dominated, although some experienced positive emotions or muted emotions. Coping responses: engaged coping (e.g. hearing aids, communication tactics) and disengaged coping (e.g. withdrawal from situations, withdrawal within situations): both had perceived advantages and disadvantages. Conclusions: This novel application of the self-regulatory model demonstrates that it can be used to capture the key psychosocial experiences (i.e. perceptions, emotions, and coping responses) of adults with mild-moderate hearing loss within a single, unifying framework.